Aplikasi Pengarsipan Data Kliping Surat Kabar Harian Bidang Hubungan Masyarakat Kepolisian Daerah Kalimantan Selatan - -, Herpendi; Saputri, Septi; Hafizd, Khairul Anwar (STMIK Palangkaraya, 2019)
The Public Relations Sub Division in the South Kalimantan Regional Police records the clipping of daily newspapers using Microsoft Excel. Clipping data is recorded and then processed and counted types of characters, sizes, pages and coverage. Each type is divided into 3 (three) categories. The types of characters consist of Positive, Negative and Neutral. The type of size consists of Length, Medium and Small. The type of page consists of Front, Middle and Back. Then the type of coverage consists of Large, Enough and less. At the time of recording, errors often occur so that the data generated is not in accordance with the results of calculations. Therefore, a system is built that can be used to record data clipping files with automatic calculation formulas to reduce the risk of errors and incompatibility of the calculation results. This system is built with web-based using the PHP programming language. System development method using Waterfall method.